Experimental Investigation of Process Parameters for Rapid Prototyping Technique (Selective Laser Sintering) to Enhance the Part Quality of Prototype by Taguchi Method. (2016) - Kumar, Nitish; Kumar, Hemant; Khurmi, Jagdeep Singh
Abstract: Rapid Prototyping has come out as the best technology in the recent times, which allows the direct conversion of CAD files into the functional prototypes where it mainly decreases the lead time to produce the physical prototype important for design verification and operational analysis by creating the prototype directly from CAD data. Part quality of the prototype in the RP technique mainly depends upon the parameters such as hatch cure depth, layer thickness, orientation, laser power, temperature, hatch spacing. Thus an attempt was made to study and optimization of process parameters governing the system which are linked with part characteristics by using the Taguchi experimental design technique. This paper proposes to characterize the influence of physical build parameters over the part quality. This paper mainly represents the influence of three parameters i.e. Laser power, Temperature and Part Orientation for the dimensional accuracy and micro-hardness of part made in Selective Laser Sintering technique by using the Taguchi technique and an orthogonal array of experiment was developed which has least number of experimental runs with above three process parameters and also made by analysis tools such as ANOVA (Analysis of Variance).